Synthesis, optical properties and theoretical modelling of discrete emitting states in doped silicon nanocrystals for bioimaging. Issue 33 (9th August 2018) - McVey, B. F. P.; König, D.; Cheng, X.; O'Mara, P. B.; Seal, P.; Tan, X.; Tahini, H. A.; Smith, S. C.; Gooding, J. J.; Tilley, R. D.
Abstract : The creation of multiple emission pathways in quantum dots (QDs) is an exciting prospect with fundamental interest and optoelectronic potential. Abstract : The creation of multiple emission pathways in quantum dots (QDs) is an exciting prospect with fundamental interest and optoelectronic potential. For the first time, we report multiple emission pathways in semiconductor nanocrystals (NCs) where the number of emission pathways desired is controlled by the number of dopant atoms per quantum dot. The origin of additional emission pathways is explained by interactions between dopant states and NC energy levels. Density functional theory (DFT) calculations of undoped 2.3 nm silicon (Si NCs) and the same NCs doped with 2 interstitial Cu atoms show good agreement to experiment. Such calculations provide valuable data to explain the changes in optical transitions due to the Cu dopant in terms of transition energies, quantum yield and dopant position as a function of dopants per NC. Changes in the optical properties of Si NCs induced by dopant concentration include extended excitation range and enhanced absorption coefficients, emission redshifts of up to 60 nm, and a two-fold increase in quantum yields up to 22%. The optical properties of doped NCs lead to significant bioimaging improvements illustrated by in vitro cell imaging, including redshifted excitation wavelengths away from natural autofluorescence and enhanced fluorescent signals.